2013
DOI: 10.1037/a0033608
|View full text |Cite
|
Sign up to set email alerts
|

When conflicts are good: Nonconscious goal conflicts reduce confirmatory thinking.

Abstract: In this article, we argue that nonconscious goal conflicts are accompanied by a mindset that has wide-ranging implications for reasoning and thinking in content areas that are not part of the conflict itself. Specifically, we propose that nonconscious goal conflicts induce a mode of processing information that increases the likelihood of approaching an issue from opposing perspectives. This hypothesis is examined by investigating the effects of nonconscious goal conflicts on confirmatory thinking, that is, a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 49 publications
(89 reference statements)
3
67
0
Order By: Relevance
“…The “conflict mindset” idea stems from this very nature of conflict (Kleiman & Hassin, ). Specifically, the idea of a conflict mindset states that internal conflicts evoke a unique information processing strategy that builds on the very nature of conflict—vacillating between two (or more) conflicting alternatives.…”
Section: The Conflict Mindsetmentioning
confidence: 99%
See 2 more Smart Citations
“…The “conflict mindset” idea stems from this very nature of conflict (Kleiman & Hassin, ). Specifically, the idea of a conflict mindset states that internal conflicts evoke a unique information processing strategy that builds on the very nature of conflict—vacillating between two (or more) conflicting alternatives.…”
Section: The Conflict Mindsetmentioning
confidence: 99%
“…Once a conflict is evoked, the cognitive procedure of considering alternatives becomes accessible, irrespective of the specific content that activated the conflict in the first place. This procedure is then applied to relevant judgments the individual has to currently make and has streamline implications for cognition, motivation, and behavior (Kleiman & Hassin, ; Savary, Kleiman, Hassin, & Dhar, ; Stern & Kleiman, ).…”
Section: The Conflict Mindsetmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition of conflict during goal pursuit has been shown to trigger consideration of broader perspectives critical thinking about goal priorities and goal pursuit (Kleiman & Hassin, 2013). Goal conflict and their coinciding mixed emotions could therefore lead to more accurate appraisals of priorities and resources, to the ultimate benefit of goal achievement.…”
mentioning
confidence: 99%
“…Accordingly, we activated a conflict outside of awareness by simultaneously priming two conflicting goals (Kleiman & Hassin, 2013), and examined whether there is an increase in systematic processing on choice in domains unrelated to the primed conflict. We demonstrated that nonconsciously activated goal conflict de creases the likelihood of selecting options associated with conflict avoidance (Experiments 1 and 4), due to a more systematic infor mation processing associated with a conflict mindset (Experiment 2), and not to other factors (Experiment 3).…”
mentioning
confidence: 99%